Young, Free and Single? - Heath, S. author. aut Link
VIII, 225 p.
Keywords: In the context of the ongoing destandardization of young people's lives, this book explores changing patterns of household formation amongst contemporary 20-somethings and the implications of these changes for the ways in which they relate to friends, parents and partners. The book points to the growing polarization between the experiences of graduates and non-graduates, and highlights changing expectations and attitudes towards intimacy and 'settling down' amongst these groups.